Characteristics of hepatocellular carcinoma in Egyptian patients with primary Budd‐Chiari syndrome. (13th September 2016) - Sakr, Mohammad; Abdelhakam, Sara M.; Dabbous, Hany; Hamed, Amr; Hefny, Zeinab; Abdelmoaty, Waleed; Shaker, Mohamed; El‐Gharib, Mohamed; Eldorry, Ahmed
Abstract: Background & Aim: Budd‐Chiari syndrome (BCS) is caused by hepatic venous outflow obstruction. This work aimed at analyzing characteristics and factors associated with development of hepatocellular carcinoma (HCC) in patients with primary BCS. Methods: A total of 348 Egyptian BCS patients were included. They were presented to the Budd‐Chiari Study Group of Ain Shams University Hospital. BCS was confirmed using abdominal Doppler US. Abdominal magnetic resonance imaging (MRI), MR venography and/or multislice computed tomography (CT) were performed to confirm all diagnoses and to assess vascular anatomy. Hepatic focal lesions detected during the study period (2005–2011) were evaluated using serum alpha foetoprotein (AFP) level, imaging features and histopathological examination. Results: Diagnosis of HCC was confirmed in 15/348 patients (4.3%). Imaging studies showed that 60% had multiple hepatic focal lesions ranging from 2 to 6.3 cm in size. The median level of serum AFP in BCS with HCC was 300 ng/mL vs 11 ng/mL in those without HCC ( P <.001). A cut‐off level >24.5 ng/mL for serum AFP showed sensitivity 80%, specificity 97.9%, positive predictive value 93.18% and negative predictive value 99.1% for detection of HCC in BCS patients. Male gender, older age, cigarette smoking, serum AFP (>24.5 ng/mL) and shrunken liver by ultrasonography were independent factors associated with HCC development. Conclusion: Male gender, older age and cigarette smoking are independent risk factors for development of HCC in BCS. Serum AFP is a good screening test in BCS.